2019
DOI: 10.9738/intsurg-d-15-00333.1
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Prognostic Factors for Lung Metastasectomy in Colorectal Cancer Patients With Previously Resected Liver Metastases

Abstract: The purpose of this study is to investigate the prognostic factors of lung metastasectomy in patients with previously resected liver metastases. Thirty-three patients underwent complete resection of lung metastases after previous liver metastasectomy from colorectal cancer between January 2004 and December 2013. In univariate analyses, all cumulative survival curves were estimated using the Kaplan-Meier method, and differences in variables were evaluated using the log-rank test. Multivariate analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Multiple investigations have shown that aggressive surgical therapies in these patients are feasible and should be pursued. [21][22][23][24] T A B L E 1 Baseline characteristics of patients with resected colorectal cancer, stratified by development of pulmonary metastasis. Metachronous lesions should also be resected and have better outcomes than synchronous metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple investigations have shown that aggressive surgical therapies in these patients are feasible and should be pursued. [21][22][23][24] T A B L E 1 Baseline characteristics of patients with resected colorectal cancer, stratified by development of pulmonary metastasis. Metachronous lesions should also be resected and have better outcomes than synchronous metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, patients may exhibit synchronous liver and lung metastases. Multiple investigations have shown that aggressive surgical therapies in these patients are feasible and should be pursued 21–24 . Metachronous lesions should also be resected and have better outcomes than synchronous metastases 25 …”
Section: Discussionmentioning
confidence: 99%